v bor'be za vlast' sovetov na Ukraine. (nojabr' 1917-1920 gg.) Sbornik dokumentov. [Pod red. E.M. Skljarenko, N.I. Suprenenko, V.S. Šlomin . sost.: V.I. Aleksandrova, T.S. Fedorova; s predisl. V.S. Šlomina].; (AN USSR, 1963)
S ill-mi, prt-mi i ukaz-mi.